2022
DOI: 10.3390/jfb13040191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bioactive Glass and Low Viscosity Resin as Orthodontic Enamel Sealer: An In Vitro Study

Abstract: The study aimed to evaluate the effect of applying fluoride bioactive glass (FBAG) and Alpha-Glaze® (resin sealer) on the shear bond strength of orthodontic brackets to enamel bonded by Transbond XT, brushing‒abrasion durability, and their protective effect against simulated cariogenic acidic attack. Materials include 135 extracted premolars that were divided into three groups—FBAG, Alpha-Glaze, and control. The shear bond strength test was measured using an Instron Universal Testing Machine. The brushing abra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Moreover, in the current study it was found that the shear stress values, regardless of the type of adhesive system, decreased significantly (T1>T2>T3) over time, which is consistent with the observations of Mitić et al [ 6 ]. The fact that the bond strength weakens over time reduces the risk of damage to the enamel when removing orthodontic brackets.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, in the current study it was found that the shear stress values, regardless of the type of adhesive system, decreased significantly (T1>T2>T3) over time, which is consistent with the observations of Mitić et al [ 6 ]. The fact that the bond strength weakens over time reduces the risk of damage to the enamel when removing orthodontic brackets.…”
Section: Discussionsupporting
confidence: 93%
“…The popularity of orthodontic treatment with fixed appliances [ 3 ] means that more and more dental adhesives for securing orthodontic devices are appearing on the market [ 4 6 ], and many types of appliances are available that differ in the construction of brackets and bands [ 7 ].…”
Section: Introductionmentioning
confidence: 99%